Study of partial shape memory effect of polymers by multicycle tests. Issue 6 (5th April 2015) - Abdallah‐Elhirtsi, Sofiane; Fitoussi, Joseph; Rashmi, Baralu‐Jagannatha; Prashantha, Kalappa; Farzaneh, Sedigheh; Lacrampe, Marie‐France; Krawczak, Patricia; Tcharkhtchi, Abbas
Abstract : In this work, an experimental investigation on a partial shape memory polymer (PSMP) which is transformed into shape memory material is presented. Multicycle shape memory tests are performed on thermoplastic polyurethane (TPU) at 70°C. At the end of each cycle, the capacity of the shape memory material increases. At the end of the first cycle, the recovery rate of TPU is only 67%; this partial shape memory effect (PSME) has been improved by successive cycles of shape memory tests. After the fourth cycle, it becomes nearly 100% shape memory material. The results of the fifth and sixth cycles confirm this modification. These original results indicate that a polymer with partial shape memory may be transformed into an SMP without any chemical modification. This increase of SME could be related to the creation of residual stresses during the tensile tests. The residual stresses are the origin of the driving force responsible for SME. POLYM. COMPOS., 36:1145–1151, 2015. © 2015 Society of Plastics Engineers